Pain Characteristics and Demographics of Patients Attending a University-Affiliated Pain Clinic in Toronto, Ontario. (2007) - Mailis-Gagnon, Angela; Yegneswaran, Balaji; Lakha, SF; Nicholson, Keith; Steiman, Amanda J; Ng, Danny; Papagapiou, Marios; Umana, Margarita; Cohodarevic, Tea; Zurowski, Mateusz
Abstract : BACKGROUND: Pain clinics tend to see more complex chronic pain patients than primary care settings, but the types of patients seen may differ among practices. OBJECTIVE: The aim of the present observational study was to describe the pain and demographic characteristics of patients attending a university-affiliated tertiary care pain clinic in Toronto, Ontario. METHODS: Data were collected on 1242 consecutive new patients seen over a three-year period at the Comprehensive Pain Program in central Toronto. RESULTS: Musculoskeletal problems affecting large joints and the spine were the predominant cause of pain (more prevalent in women), followed by neuropathic disorders (more prevalent in men) in patients with recognizable physical pathology. The most affected age group was in the 35- to 49-year age range, with a mean pain duration of 7.8 years before the consultation. While 77% of the Comprehensive Pain Program patients had relevant and detectable physical pathology for pain complaints, three-quarters of the overall study population also had significant associated psychological or psychiatric comorbidity. Women, in general, attended the pain clinic in greater numbers and had less apparent physical pathology than men. Finally, less than one in five patients was employed at the time of referral. CONCLUSIONS: The relevance of the data in relation to other pain clinics is discussed, as well as waiting lists and other barriers faced by chronic pain patients, pain practitioners and pain facilities in Ontario and Canada.